Red Seaweeds as Resource of Bioactive Compounds and Therapeutic Potential: a Review on Anticancer Agents - Warsi, Warsi; Narwanti, Iin; Ahmed, Qamar Uddin (Universitas Ahmad Dahlan, 2025)
The use of natural compounds derived from macroalgae constitute an alternating strategy in the creation of anticancer medications. Seaweed refers to macroalgae. Red seaweeds are rich in bioactive compounds, including alkaloids, carotenoids, mycosporine-like amino acids, phycobiliproteins, polyphenols, polysaccharides (carrageenan, porphyran), and lipids. Some of these bioactive compounds have demonstrated a unique chemical framework. The bioactive compounds have been investigated as an anticancer potential in vitro studies. Among these compounds content, polyphenols are the most promising as an anticancer, due to their abundance in the red seaweeds. This review provides bioactive compounds from red seaweeds and their natural sources. The review involves papers published from 2010 to 2025. The study might be used as a reference in development of red seaweed extracts in the future which include preclinical and clinical investigations, standardizations and formulations, molecular mechanisms as anticancer and toxicity studies. Keywords: Anticancer, bioactive compound, macroalgae, pharmacological activity, seaweed